ISLAMIC COMMUNITY EMPOWERMENT THROUGH ECONOMIC DEVELOPMENT AT THE VILLAGE-OWNED ENTERPRISE (BUMDES) 'SEJAHTERA' IN JANGKANG VILLAGE, RIAU - Izham, Khairul; Faizal, Faizal; Jauhari, Tontowi (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2024)
This study aims to describe and analyze the community empowerment process and economic development strategies implemented through the Village-Owned Enterprise (BUMDes) 'Sejahtera' in Jangkang Village, Bantan District, Bengkalis Regency, Riau Province. This research uses a descriptive qualitative method with data collected through interviews, observations, and documentation. Data analysis was conducted using data reduction, data presentation, and conclusion drawing, with validity tested through triangulation of techniques and sources. The findings reveal that the community empowerment process in BUMDes 'Sejahtera' is carried out through three main stages: (1) increasing community awareness, (2) capacity building for individuals and groups, and (3) implementing empowerment activities. The economic development strategies applied include: (1) creating a supportive climate for strengthening local capacities and safeguarding local assets, and (2) implementing rural development programs based on local needs. This study offers novelty in its structured participatory approach to active community involvement, presenting a potential model for replication in other villages. Practically, the findings provide valuable guidance for BUMDes managers and policymakers in designing more effective empowerment programs, particularly in enhancing the economic independence of rural communities.